Pemberdayaan Entrepreneurship Melalui Penerapan Branding Jamu Widjaya - Decky Rochmanto; Shahnaz Surayya; Arum Dina Prajna Paramita; Khoirur Rozaq; Mayang Tiara; Nina Febriani; Rika Mawati; Achmad Eriel Pangestu; Siti Rois Yuliasuti; Ahmad Naufal Ilmi Fasya (Universitas Islam Nahdlatul Ulama Jepara, 2022)
During the pandemic, people need additional supplements to strengthen their immune system. Supplements that are good for the body are those made from natural ingredients by utilizing existing natural resources. One of these supplements is traditional herbal medicine whose ingredients are passed down from the ancestors of the Indonesian people. This service activity aims to market herbal products in order to increase public interest in increasing immunity through natural supplements in the form of traditional herbs without preservatives so that they are safe for body health. In addition, branding can make the surrounding community have an entrepreneurial spirit by utilizing the existing natural potential. The partners chosen in this community service community service program are productive partners, namely UMKM Jamu Widjaya. The method of implementing this service is Asset Based Community Development (ABCD) which consists of five steps, namely discovery, dream, design, define and destiny. The results of this service can be seen that there are significant changes, ranging from the quality of herbal products to long-lasting syrups, the packaging / packaging becomes more attractive, because there is a re-designed logo to the manufacture of neon boxes. The marketing method, which was originally only through word of mouth and telephone, has now entered the marketplace, so that consumer interest in products has increased compared to before the existence of branding. This community service program has proven to be very helpful for Jamu Widjaya in developing herbal products into the form of herbal syrup and an increase in sales can be seen during the program running from week 3 to week 4.